The comparison of Shape factor and mean toric keratometry between pterygium and normals - Hilmi, Mohd Radzi; Nasir, Mardhiah Syazwani; Mohd. Kamal, Khairidzan; Che Azemin, Mohd Zulfaezal; Norazmar, Nur Ain; Musa, Nur Hidayah; Maruziki, Nur Nabilah (International Islamic University Malaysia (IIUM), 2019)
Introduction: The aim of this paper is to determine the changes in overall anterior corneal curvature between unilateral primary pterygium and normal adults utilizing shape factor and mean toric keratometry. Methods: Total of 60 participants comprises of 30 unilateral primary pterygium eyes from 30 pterygium patients and 30 normal adults were recruited in this study. Diagnosis and classification of primary pterygium were done by a consultant ophthalmologist (KMK). Standard optometric examinations were performed in all participants. Shape factor (SF) and toric mean keratometry (TKM) were objectively measured using a corneal topographer. Three measurements based on best image quality for SF and TKM were taken by single operator in a same visit. Difference for both SimK and CIM parameters between primary pterygium and normal groups were determined via independent T-test. Results: Overall mean and standard deviation (n = 60) of SF and TKM were found higher in primary pterygium group (0.79 ± 0.09 and 49.09 ± 5.42 D) compared to normal (0.37 ± 0.09 and 44.73 ± 2.02 D) respectively. Independent T-test results showed significance difference in SF and TKM values between primary pterygium groups and normal (both P < 0.001). Conclusions: Both SF and TKM can be used as a tool in describing early changes of pterygium on the anterior corneal surface. Advance pterygium could induce significant increment in both SF and TKM.